Economic Prospects of Cross-Border Electricity Trade Between Nepal and India - Dangal, Dil Nath; Chapagai, Shiva Dutta; Ghimire, Krishna Prasad (Economic Review of Nepal, 2022)
This study focuses on exploring the economic opportunities and potential challenges of cross-border electricity trade between Nepal and India. The main focus is on the transmission infrastructure, economic prospects, regulatory frameworks, and challenges involved. The study was conducted through secondary data analysis and descriptive research methods, to explore the strategic importance of electricity trade for Nepal, considering its abundant hydropower potential and geographical advantages. The existing transmission lines, infrastructure, and the role of private sector involvement in facilitating trade were examined. Moreover, the study discussed the seasonal demand variations between the two countries and the regulatory hurdles that need to be addressed for successful trade implementation. The finding highlights the potential economic benefits of electricity trade and emphasizes the need for clear guidelines, infrastructure development, and effective cooperation to overcome challenges and maximize trade’s positive impacts on economic growth and trade balance between India and Nepal.